TEACHING PROFESSIONALIZATION IN XXI CENTURY: CHALLENGES AND POSSIBILITIES IN CRISIS TIMES - Bonatto Rufino, Luiz Gustavo; Neto, Samuel de Souza [UNESP] (Fundacao Univ Tocantins, 2021)
In unusual times, the professions, as well as the concept of work itself, take on diversified shapes and undergoes processes of reframing. In the case of teaching, in order to understand teaching work today, new ways are needed to establish meaning in the training processes. In this context, the present work sought to relate the current perspectives linked to the movement of teaching professionalization with the field of teacher education in Brazil. For this, this theoretical essay was divided into two parts: in the first we seek to establish the main historical assumptions linked to the idea of teaching professionalization and in the second we seek to base such ideas within the theoretical perspective of teaching work, proposing interfaces with the contexts of training. We conclude that changes in perspective are necessary within the field of teacher education so that there would be greater understanding about the professionalization process and teaching work as a structuring axis of professional practice.
Keywords: Teacher's education; Teachers training; Teaching professionalization; Teachers work; Profession